Identification of bioactive compounds and encapsulation of bee bread from Heterotrigona itama using a spray dryer with its antioxidant activity - EKA SARI; DYAH AYU SURYA WARDHANI; VIVI AGUSTINA; AGUSSALIM AGUSSALIM; LUTHFI HAKIM; RIKA WULANDARI; NENDYO ADHI WIBOWO; LEE SUAN CHUA (Society for Indonesian Biodiversity, 2024)
Abstract. Sari E, Wardhani DAS, Agustina V, Agussalim, Hakim L, Wulandari R, Wibowo NA, Chua LS. 2024. Identification of bioactive compounds and encapsulation of bee bread from Heterotrigona itama using a spray dryer with its antioxidant activity. Biodiversitas 25: 2857-2865. Stingless bee produces honey, propolis, and bee bread. Bee bread is known to have a high antioxidant. This study uses a spray dryer and its antioxidant activity, phytochemical, and bioactive compounds; therefore, it aims to encapsulate bee bread from Heterotrigona itama Cockerell 1918. The encapsulation of bee bread used several encapsulants, such as starch, lactose, and maltodextrin, in several formulas. The physical characterization was performed by analysis of hygroscopic properties by Scanning Electron Microscopy (SEM), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and DPPH antioxidant. The results showed that bee bread contains bioactive compounds, such as saponins, alkaloids, carbohydrates, quinones, flavonoids, tannins, phenols, and ninhydrin. The best encapsulant was a combination of starch and lactose with the formula 50:50 (% w/w), which has low hygroscopic properties. SEM analysis shows that bee bread does not bond well with filler at a 10.817 to 20.244 µm diameter. XRD analysis obtained a product crystallinity level of 71.0819%. FTIR analysis shows that bee bread has the most complex functional group, which was characterized by the presence of a wave at the point of 1,115.68 cm-1, which indicates the presence of a group (C?O?C) that shows the spectrum of flavonoid group compounds with antioxidant activity of 588.402 ppm.